Patterns and mechanisms of repeat drainages of glacier-dammed Dań Zhùr (Donjek) Lake, Yukon - Moya Painter; Luke Copland; Christine Dow; Will Kochtitzky; Dorota Medrzycka (Arctic Science, 2024)
Dań Zhùr (Donjek) Glacier is a surge-type glacier that undergoes cyclical periods of rapid advance over ∼1–2 years, followed by retreat for ∼10 years. Since the 1990s, the advances have caused the formation of ice-dammed Dań Zhùr Lake, which has filled and drained in summers following a surge event. Here, we report how these drainages initially occur through a subglacial channel under the glacier terminus, which then typically closes the following winter, enabling another lake to form and drain the next summer. However, our remote sensing and field observations indicate that after several drainage events, a subaerial ice canyon is formed through the glacier terminus, which prevents another lake from forming until after the glacier surges again. We predict that the next surge of Dań Zhùr Glacier will occur around the mid-2020s, causing the formation of a larger Dań Zhùr Lake during the following quiescent phase because, despite periodic advances, a long-term trend of glacier recession is exposing a larger basin for the lake to form in. However, each subsequent surge is causing less terminus advance than the previous one, until ultimately the surges will be insufficient to dam Dań Zhùr Chù’ (Donjek River), and lakes will cease to form.